Geometrically controlled liquefied capsules for modular tissue engineering strategies - Nadine, Sara (2022)
A plethora of bioinspired cell-laden hydrogels are being explored as building blocks that once assembled are able to create complex and highly hierarchical structures recapitulating the heterogeneity of living tissues. Yet, the resulting 3D bioengineered systems still present key limitations, mainly related with limited diffusion of essential molecules for cell survival, which dictates the failure of most strategies upon implantation. To maximize the hierarchical complexity of bioengineered systems, while simultaneously fully addressing the exchange efficiency of biomolecules, the high-throughput fabrication of liquefied capsules is proposed using superhydrophobic-superhydrophilic microarrays as platforms to produce the initial structures with high fidelity of geometry and size. The liquefied capsules are composed by i) a permselective multilayered membrane; ii) surface-functionalized poly(ε-caprolactone) microparticles loaded into the liquefied core acting as cell adhesion sites; and iii) cells. It is demonstrated that besides the typical spherical liquefied capsules, it is also possible to obtain multi-shaped blocks with high geometrical precision and efficiency. Importantly, the internal gelation approach used to produce such blocks does not jeopardize cell viability, evidencing the mild conditions of the proposed cell encapsulation technique. The proposed system is intended to be used as hybrid devices implantable using minimally invasive procedures for multiple tissue engineering applications.